Misfit phase (BiSe)1.10NbSe2 as the origin of superconductivity in niobium-doped bismuth selenide - Hadermann, J; Kamminga, ME; Batuk, M; Clarke, SJ (Springer Nature, 2020)
Topological superconductivity is of great contemporary interest and has been proposed in doped Bi2Se3, in which electron-donating atoms such as Cu, Sr or Nb have been intercalated into the Bi2Se3 structure. For NbxBi2Se3, with Tc ~ 3 K, it is assumed in the literature that Nb is inserted in the van der Waals gap. However, in this work an alternative origin for the superconductivity in Nb-doped Bi2Se3 is established. In contrast to previous reports, it is deduced that Nb intercalation in Bi2Se3 does not take place. Instead, the superconducting behaviour in samples of nominal composition NbxBi2Se3 results from the (BiSe)1.10NbSe2 misfit phase that is present in the sample as an impurity phase for small x (0.01 ≤ x ≤ 0.10) and as a main phase for large x (x = 0.50). The structure of this misfit phase is studied in detail using a combination of X-ray diffraction and transmission electron microscopy techniques.